Institutional experience of mucormycosis over a period of 10 years - retrospective case series - MS, Soumya; Menezes, Vishma Hydie; VV, Sreenivas; AM, Balasubramanya (International Journal of Advances in Medicine, 2017)
Background: Mucormycosis is an invasive fungal infection seen in immunocompromised patients. Most common presentation is face or orbital pain, headache, lethargy, visual loss, proptosis, or palatal ulcer. Because of its angioinvasive properties, it can rapidly spread to intracranial tissues and orbit. It can lead to fatal complications such as blindness, intracranial infections, convulsions and even death. Aim of current study was to diagnose this condition; a high index of suspicion is required. Blackish crusts are characteristically seen and Potassium hydroxide (KOH) staining of these crusts can give a rapid diagnosis. Methods: Study Design was retrospective review of the charts. We reviewed the charts between January 2001 and December 2010 and compiled together 60 cases of mucormycosis. Results: The most common presentation was orbital cellulitis. Some patients presented with features of acute sinusitis. The most common cause of immunosuppression was diabetes mellitus. Patients were started on amphotericin. The prognosis was bad in 7 patients who lost vision and 8 patients died. Conclusion: Diagnosis in the early stage needs a high degree of suspicion. The underlying illness, the time between the onset of the disease and the establishment of treatment, and the occurrence of cerebral ischemic events play a role in worse survival rates.